2011
DOI: 10.2105/ajph.2010.191668
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Analysis of US Racial/Ethnic Disparities in Smoking Behaviors, Smoking Cessation, and Cessation-Related Factors

Abstract: Specific needs and ideal program focuses for cessation may vary across racial/ethnic groups, such that approaches tailored by race/ethnicity might be optimal. Traditional conceptualizations of cigarette addiction and the quitting process may need to be revised for racial/ethnic minority smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
286
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(313 citation statements)
references
References 35 publications
23
286
4
Order By: Relevance
“…55 During 1967During -1970, when the Fairness Doctrine antismoking messages appeared on television and radio, cessation increased for all four groups but especially for white males and females. The data in Figure 1 and many of the population-based cross-sectional studies 2,17,18,22,26,[48][49][50][51][52][53] likely reflect, at least in part, the "head start" that white males and females had in terms of quitting smoking. Among all four groups, cessation rates increased during the 1970's and 1980's, 54 which is consistent with the increasing slopes for both whites and African Americans that are seen in Figure 1.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…55 During 1967During -1970, when the Fairness Doctrine antismoking messages appeared on television and radio, cessation increased for all four groups but especially for white males and females. The data in Figure 1 and many of the population-based cross-sectional studies 2,17,18,22,26,[48][49][50][51][52][53] likely reflect, at least in part, the "head start" that white males and females had in terms of quitting smoking. Among all four groups, cessation rates increased during the 1970's and 1980's, 54 which is consistent with the increasing slopes for both whites and African Americans that are seen in Figure 1.…”
Section: Discussionmentioning
confidence: 89%
“…As shown in Figure 1 and previously by Fiore and his colleagues, 3 the percentage of ever-smokers who have quit has consistently been higher among whites than African Americans, a finding that is supported from studies in individual years. 2,17,18,22,26,[48][49][50][51][52][53] One study, 51 and an analysis presented in Table 34 of Chapter 2 of the 1998 Report of the Surgeon General, 2 indicate that the differences by race persist even after statistical adjustment was made for variables such as age, gender, and indicators of socioeconomic status (SES). Burns and his colleagues presented birth cohort analyses of whites and African Americans born during the 20th century that help explain these disparities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, for AA who are daily smokers, Addictive Smoking, Pleasure to Smoke, Handling, and Social Smoking would be important to address in treatment. AA tend to have difficulty quitting smoking (Stahre, Okuyemi, Joseph, & Fu, 2010;Trinidad, Pérez-Stable, White, Emery, & Messer, 2011) underscoring the value of gaining insight into their RS. Finally, among Whites who are nondaily smokers, clinicians should particularly attend to Pleasure to Smoke, Handling, and Social Smoking RS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent nationwide study found that African Americans were only half likely to quit smoking or use nicotine replacement therapy compared to White Americans. 65 There are several environmental factors that may foster the increase in recent years of current smoking prevalence among urban African Americans: targeted advertisements from tobacco companies in poor neighborhoods, cigarettes being sold in urban neighborhood stores more often than fresh food, and easy access to single cigarettes on the street that averts challenging tax policies. 4,66,67 A recent study also shows a strong association between high exposure to tobacco retail outlets and smoking initiation among adolescents in major urban cities.…”
Section: Discussionmentioning
confidence: 99%